A new case of trombiculiasis caused by Eutrombicula daemoni Bassini-Silva & Jacinavicius, 2018 (Trombidiformes: Trombiculidae) in a dog from Brazil - Santos-Rodrigues, Rodrigo; Bassini-Silva, Ricardo; Huang-Bastos, Matheus; Araujo, Karine M. de Q.; de Carvalho, Flavia C. G.; Brêtas, Guilherme; Jacinavicius, Fernando de C. (Entomological Communications, 2021)
Chiggers are ectoparasites and can cause severe dermatitis in their hosts, known as trombiculiasis. Besides that, these mites can be vectors of bacteria of the genus Orientia, in various regions of the world. The genera Eutrombicula Ewing, 1938 is currently represented by more than 80 species worldwide. Species of this genus are recorded parasitizing reptiles, birds, and mammals. One of this species, Eutrombicula daemoni Bassini-Silva & Jacinavicius, 2018 was recently described causing trombiculiasis in a dog. Our goal is to report a new case of a dog’s trombiculiasis, including a new locality record for E. daemoni in Brazil. In May 2021, a female Shih-Tzu dog with three years old and with access to the forest of the Santa Tereza municipality, southeastern Brazil, sought veterinary medical attention for intense itching and erythema in the facial region. Mites were collected directly from the face of the dog. These materials were slide-mounted and deposited in the Acarological Collection of the Butantan Institute (IBSP). The material extracted from the dog was examined and identified as E. daemoni. Part of the fixation site tissue of the dog was collected, showing the feeding tube produced by the enzymatic reaction of saliva by the mite, known as a stylostome. In this report, we emphasize the occurrence of trombiculiasis in domestic animals that have access to forest regions, places that unfed chigger larvae live. Additionally, this record represents a new locality record for E. daemoni to the Espírito Santo State, Brazil.